STRENGTHENING THE INTEGRITY OF REGIONAL HEAD CANDIDATES THROUGH THE COMPETENCE TEST MECHANISM IN REGIONAL HEAD ELECTIONS (PILKADA) - Wahyu Hindiawati; Mukhammad Soleh; Sri Ayu Irawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Regional Head Elections (Pilkada) are a crucial instrument in local democracy to produce regional leaders with integrity and capacity. However, in practice, Pilkada in Indonesia is still plagued by various problems, such as high political costs, rampant money politics, and weak recruitment mechanisms for regional head candidates, which result in low integrity and increased risks of corruption. This study aims to analyze the implementation of competency testing mechanisms as an instrument to strengthen the integrity of regional head candidates and to formulate an ideal model for strengthening integrity within the framework of the Indonesian constitutional system. The research method used is normative juridical with a statutory and conceptual approach, through an analysis of related regulations and relevant legal literature. The results show that a structured, objective, and accountable competency testing mechanism can be a strategic instrument in assessing aspects of integrity, leadership capacity, national insight, managerial ability, and commitment to eradicating corruption. The proposed ideal model is based on the principles of the rule of law, democracy, and good governance, and is supported by strong regulations, the involvement of independent institutions, transparency, and public participation. Thus, the implementation of this mechanism is expected to improve the quality of local democracy and produce regional heads who are professional, have integrity, and are oriented towards the interests of the community.